IMPLEMENTATION OF ZERO WASTE CONCEPT IN MALAYSIA: FROM CONTRACTORS’ PERSPECTIVE - Sheikh Ilmi, Habizah; Yee, Jing Wen; Kam, Kenn Jhun; Lim, Tze Shwan; Soon, Lam Tatt (PLANNING MALAYSIA, 2024)
Construction waste is one of the major contributions to severe environmental issues. However, this construction and demolition (C&D) waste issue is often neglected by the stakeholders. Instead, they focus more on cost, time and quality as their priority. In Malaysia, the lack of knowledge and awareness of sustainable zero waste practices have become a major obstacle to sustainable development in the construction industry. To address this, the implementation of Zero Waste concept should be widely promoted to reduce the solid waste production and mitigate the depletion of natural resources. Hence, this study is to identify the challenges of implementing zero waste concept among the contractors. This research focuses on building contractors by using a quantitative research method to collect data from the targeted population. The findings of the study highlight that waste reduction, curbing illegal dumping and reducing public health risks are the primary concerns in relation to the Zero Waste concept. The study reveals that contractor’s attitude and reluctant behaviour, inadequate policies and the absence of mandatory zero waste management are the main barriers for the implementation of zero waste concept in Malaysia. The government should play an important role to develop C&D waste concept and to identify suitable C&D waste models which can be used in Malaysia. By adopting zero waste concept, the construction industry in Malaysia can move towards a more sustainable future and develop its sustainability targets under Sustainable Development Goal (SDG) 12.